2007
DOI: 10.1093/molehr/gam021
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone induced progesterone withdrawal reveals novel regulatory pathways in human endometrium

Abstract: In women, a single dose of the antiprogestin mifepristone (RU486) in the secretory phase rapidly renders the endometrium unreceptive and is followed by endometrial breakdown and menstruation within 72 h. This model provides a system to identify progesterone-regulated genes, which may be involved in endometrial receptivity and the induction of menstruation. We used cDNA microarrays to monitor the response of the endometriuim over 24 h following administration of mifepristone in the mid-secretory phase. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
107
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 61 publications
14
107
2
1
Order By: Relevance
“…Table 6 gives a list of common gene products that appeared to be regulated by progesterone in previous reports and those reported to display differential abundance in the present study. Now, we report for the first time that a new cohort of 28 gene products were affected in implantation-stage endometrium, following early luteal-phase administration of mifepristone in the present study, and those that were not reported to be affected by progesterone in earlier array-based studies using the model of comparative study between prereceptive and receptive stage endometria (Carson et al 2002, Kao et al 2002, Borthwick et al 2003, Riesewijk et al 2003, Giudice 2004, Mirkin et al 2005, Talbi et al 2006, Sherwin et al 2007). Out of nine gene products that were subjected to realtime RT-PCR quantification, seven (CD44, CSF1, distal less homeobox 4 (DLX4), enigma, KDR, leptin receptor, macrophage migration inhibitory factor (MIF)) are reported here as novel candidates, while two (mucin 1 (MUC1) and uteroglobin) have been reported earlier (Table 6).…”
Section: Discussionsupporting
confidence: 51%
“…Table 6 gives a list of common gene products that appeared to be regulated by progesterone in previous reports and those reported to display differential abundance in the present study. Now, we report for the first time that a new cohort of 28 gene products were affected in implantation-stage endometrium, following early luteal-phase administration of mifepristone in the present study, and those that were not reported to be affected by progesterone in earlier array-based studies using the model of comparative study between prereceptive and receptive stage endometria (Carson et al 2002, Kao et al 2002, Borthwick et al 2003, Riesewijk et al 2003, Giudice 2004, Mirkin et al 2005, Talbi et al 2006, Sherwin et al 2007). Out of nine gene products that were subjected to realtime RT-PCR quantification, seven (CD44, CSF1, distal less homeobox 4 (DLX4), enigma, KDR, leptin receptor, macrophage migration inhibitory factor (MIF)) are reported here as novel candidates, while two (mucin 1 (MUC1) and uteroglobin) have been reported earlier (Table 6).…”
Section: Discussionsupporting
confidence: 51%
“…In contrast, CTNNB1 expression in myometrial and fibroid cells were not affected by progesterone and/or RA treatments. Several studies report that members of the Wnt signalling pathway, but not CTNNB1 itself, are regulated by progesterone in human endometrial cells (Tulac et al 2006, Catalano et al 2007, Kane et al 2008. Therefore, the progesterone-associated effects on the CTNNB1 pathway in the endometrium may be cell-type specific and not affect myometrial cells.…”
Section: Nr2f2 and Ctnnb1 In Uterine Fibroidsmentioning
confidence: 99%
“…However, this model does not reflex the steroids dynamics occurring in vivo. Tissue explants are appropriate for evaluating immediate responses in human endometrium to ovarian steroids ex vivo but do not fully address the entire set of genes associated to embryo implantation (Catalano et al 2007, Dassen et al 2007a. The endometrial response to 200 mg of mifepristone in day LHC8 was evaluated in women after 6 or 24 h of treatment (Catalano et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue explants are appropriate for evaluating immediate responses in human endometrium to ovarian steroids ex vivo but do not fully address the entire set of genes associated to embryo implantation (Catalano et al 2007, Dassen et al 2007a. The endometrial response to 200 mg of mifepristone in day LHC8 was evaluated in women after 6 or 24 h of treatment (Catalano et al 2007). Although this model was designed to identify P 4 -regulated genes involved in the endometrial receptivity, also pinpoints transcripts related to the induction of menstruation, introducing a confounding factor in the determination of uterine receptivity genes.…”
Section: Introductionmentioning
confidence: 99%